COMMUNITY EDUCATION FROM A SOCIAL WORK PERSPECTIVE: SUSTAINABLE SOLUTIONS TO SOCIAL PROBLEMS - Nike Kamarubiani; Sakroni Sakroni (Adisam Publisher, 2025)
In order to solve a variety of social issues using a community-based strategy, community education is crucial. From the standpoint of social work, community education seeks to enable marginalised people and groups to deal with social issues on their own, in addition to enhancing literacy. The purpose of this literature review is to examine how community education may be used to address a range of social issues and to pinpoint practical implementation techniques. By examining several scholarly publications, books, and research papers pertaining to social work and community education, this study employs the literature review technique. According to the study's findings, community education significantly improves economic independence, lowers poverty, raises social awareness, and protects vulnerable populations. Its execution is still fraught with difficulties, however, including a lack of funding, inadequate regulations, and poor community involvement. Therefore, to guarantee the survival of community education as a means of addressing social issues, more inclusive policies and cooperation from many stakeholders are required.